Dielectric transition and ferroelectric properties of graphene oxide-barium titanate nanocomposites. Issue 4 (April 2017) - Kavinkumar, T.; Senthilkumar, P.; Dhanuskodi, S.; Manivannan, S.
Abstract: Graphene oxide (GO)-barium titanate (BT) composite was prepared through sonication process at room temperature. The temperature dependent dielectric properties and transition of GO with different pellet thickness were studied. Electrical properties of GO-BT composites with different weight percentages of GO and BT (2:1, 1:1 and 1:2) from 30 to 200 °C were investigated. The dielectric constant was calculated as 3701 and 1296 for GO(2)-BT(1) and GO(1)-BT(1) composites respectively which are higher than that of BT at 1 kHz. The improvement of ε' is attributed to the formation of microcapacitors by GO sheets segregated by BT particles. Curie temperature of BT was suppressed in the composites and effect of GO on the dielectric properties of the composite is predominant. The dielectric peaks of GO at 50 and 170 °C were gradually shifted to high and low temperatures respectively with increasing BT content. Furthermore, polarization (P) vs electric field (E) was measured at room temperature specifying the decrease in ferroelectricity of composites from that of BT, indicating the highly conducting nature of these samples. The increasing content of GO in composite leads to decrease in remnant polarization because the introduction of GO would weaken the ferroelectricity of the composite. The present findings suggest that the new composite can be useful for fabrication of flexible electronic devices and high dielectric-based electronic and energy storage devices.